Positive Relationship Between Inclusive Students in Science Learning Based on Demographic Data in Inclusive Elementary School - Luh Armita Cahya Lestari; Putu Nanci Riastini; Dewa Gede Firstia Wirabrata (Jurnal Ilmiah Sekolah Dasar, 2026)
The low level of interaction between deaf (kolok) students and regular students in science learning, caused by differences in communication methods, limited inclusive learning support, and a lack of collaborative activities, has resulted in suboptimal positive relationships in inclusive classrooms. This study aimed to describe the level of positive relationships between kolok students and regular students and to analyze them based on gender and age. The research employed a quantitative approach with a descriptive design. The sample consisted of 38 students, including 8 kolok students and 30 regular students. Data were collected using the PERMA Profiler instrument and analyzed using descriptive statistics. The results showed that the average score of the Relationship dimension was 6.7, which fell within the low to normal category. Regular students demonstrated higher positive relationship scores, ranging from 7.4 to 7.6, while kolok students were in the very low category, with scores between 4.0 and 4.3. Analysis based on gender and age revealed relatively similar patterns, with the Meaning dimension showing the highest scores (7.1–7.5) and Happiness the lowest (5.2–5.6). In conclusion, communication barriers and limited learning support affect the quality of positive relationships among students in inclusive classrooms. The implication is that science learning needs to be designed to be more inclusive, collaborative, and oriented toward strengthening the social-emotional development of kolok students.